Witchcraft, Gender and Society in Early Modern Germany - Durrant, Jonathan B. (Brill, 2021)
Using the example of Eichstätt, this book challenges current witchcraft historiography by arguing that the gender of the witch-suspect was a product of the interrogation process and that the stable communities affected by persecution did not collude in its escalation. Readership: All those interested in the history of witch persecution, gender history, the history of the Catholic Reformation, and the history of early modern Germany.